(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
Background: Central Nervous System WHO grade 4 glioblastoma is a highly malignant brain tumor with a poor prognosis. The complex three-dimensional architecture of glioblastoma, consisting of cell-cell and cell-matrix assemblies of tumor cells, stromal cells, and extracellular matrix contributes to a highly dynamic microenvironment that resists current therapeutic approaches. Here, we established a 3D biomimetic bioprinting approach with patient-derived glioblastoma cell lines to mimic the natural tumor microenvironment for preclinical targeted therapy. Methods: Two different hydrogels (Alginate/Gelatine 3%/15%, GelMa, 4%) were used to evaluate biocompatibility. Patient-derived iRFP-680-transduced glioblastoma cells were suspended in the hydrogels and printed into scaffolds. Tumor cell growth and viability within the scaffolds were monitored for 28-days. Scanning electron microscopy was performed for structural analysis. A preliminary treatment approach was done with the standard of care drug temozolomide (TMZ 10 µM) and the CDK4/6 inhibitor abemaciclib (1 µM). Viability and LDH release were quantified. Results & Conclusion: The hydrogel compositions showed good printability. A direct comparison between the two hydrogels showed a comparable growth pattern, i.e. constant growth over a period of 21 days and a steady state until day 28. Scanning electron microscopy confirmed cellular integrity within the scaffold and the formation of small cell clusters with large pores within the matrix. In a preliminary drug response analysis, we successfully confirmed our previous results from 2D and 3D cultures. The preliminary 3D biomimetic bioprinting model proved to be a promising platform with good cell-material interaction for nutrient and substance exchange. For advanced preclinical drug screening, we aim to improve the culture conditions by incorporating vessels, non-malignant microglia and astrocytes, and by applying dynamic cell culture conditions.